The Effect of Price Discount, Store Atmosphere and Bonus Pack on Purchase Decisions (Study on Carefour Consumers) - Aryani Sairun; Sugito Sugito (ProBisnis : Jurnal Manajemen, 2023)
From the initial research that the researchers did and from the information obtained and observations made, it can be said that there were differences in consumer purchasing decisions on Dettol and Lifebuoy soap products intended for public health. The purpose of this research is to find out whether the price discount, store atmosphere and bonus pack on purchasing decisions (study on consumers Carefour). From the research results show that the value count for X1 (0.751 <1.984) and Sig (0.455> 0.05), then the price discount does not significantly influence the purchase decision. For the value of X2 obtained tcount (3.946> 1.984) and Sig (0.000 <0.05), thus the store atmosphere has a significant effect on purchasing decisions. For the value of X3 obtained t count (13.959> 1.984) and Sig (0.000 <0.05), thus the bonus pack has a significant effect on purchasing decisions. The calculated F value is 132.280 greater than F table (n - k - 1) = 2.696) and sig F <5% (0.000 <0.05), this means that simultaneously the price discount, store atmosphere and influential bonus pack variables simultaneously. significant to purchasing decisions. As a suggestion that can be raised, among others, the company should pay attention to the employee's discount price, where the price discount greatly affects the purchase decision both personally and for the company as a whole. significant to purchasing decisions.